GLUCOSE UPTAKE BY ISOLATED PARTICLES FROM RAT EPIDIDYMAL ADIPOSE TISSUE CELLS - Carter, James R. (1969)
A microsomal fraction from isolated adipose tissue cells has been prepared which possesses many features indicating the presence of a functional glucose transport system: (1) D-glucose is both taken up and released more rapidly than L-glucose at all temperatures, but at 42° L-glucose uptake reaches the level of D-glucose after prolonged incubation; (2) D-glucose uptake is inhibited by a specific inhibitor of glucose transport, phlorizin, while L-glucose uptake is unaffected; (3) Preincubation of the preparation at 42°C has no effect on L-glucose uptake but partially inhibits D-glucose uptake; (4) Equilibrium uptake studies show a linear relationship between the final level of D-glucose taken up and D-glucose concentration in the medium; and (5) Preloading the membrane preparation with unlabeled D-glucose leads to a more rapid uptake of radioactive D-glucose. These findings are interpreted as showing the presence in the microsomal particles of a specific, bidirectionally functioning D-glucose transport system superimposed on uptake of both sugars by passive diffusion or “leaks.” The retained D-glucose can be eluted from the membrane preparation and shown to be the unphosphorylated sugar.